Why Does New Testament Textual Criticism Matter? Refined Definitions and Fresh Directions. (June 2014) - Epp, Eldon Jay
New Testament textual criticism often has been dismissed as an esoteric scholarly discipline that is best avoided by clergy, students–even scholars–and better left to experts. The complexities involved in fulfilling textual criticism's first goal–identifying the earliest attainable text in each set of variant readings–can be demystified, however, (1) by facing and understanding those complexities and (2) by testing and illustrating the methods employed. Furthermore, a refined definition of the goal opens the way for correcting the long-standing neglect of rejected variant readings and for emphasising the enrichment afforded by recovering the stories that these readings have to tell about real life-issues in the early church, namely, multiple interpretations of theological questions (such as Christology) and of ethical, liturgical, and social practices (such as divorce and remarriage). The results offer fresh and fascinating glimpses of the dynamism in early Christianity.